Early diagnosis of iron deficiency in pregnancy and prevention of anemia (Research, Society and Development, 2022)
The most vulnerable group for the development of iron deficiency anemia in pregnant women, due to the high need for iron, as a result of the rapid expansion of both tissues and the production of erythrocytes. The gestational anemias generate deleterious consequences, being related to the low weight of the newborn, as well as prematurity, and to a lower concentration of hemoglobin. Also, the objective of the study is to find out about the early diagnosis of iron deficiency during gestation and the prevention of anemia through a bibliographic review. The data collection was carried out by means of an electronic search, in the National Library of Medicine (PUBMED), Scientific Electronic Library Online (SCIELO) and Latin American and Caribbean Literature in Health Sciences (LILACS) databases. To compare the search for two dice, we used the Descriptors of Ciências da Saúde (DeCS): Risk Factors. Anemia. Gravidity. The boolean operators OR and AND are also used together with the descriptors. Through the study, it is clear that it is necessary to implement programs aimed at nutritional guidance for pregnant women with a view to preventing nutrient deficiencies, mainly iron, in order to minimize the risk of anemia. It is up to the pharmacist to participate in providing guidance on iron food sources and ways to enhance its use, as well as explaining the risks of anemia and the importance and need for iron replacement during pregnancy. As nutritional guidance we must have a preventive approach for or control iron deficiency and pregnancy anemia, directing the information to adolescents and women in reproductive age, with the aim of increasing the organic mineral reserves of the population.